Lafaz Yahudi dalam Al-Qur’an - Zuherni Abubakar; Muhammad Amar bin Mohd Sabri (Program Studi Ilmu Al-Qur'an dan Tafsir Fakultas Ushuluddin dan Filsafat, UIN Ar-Raniry, 2019)
Judaism is one of the terms mentioned in the Koran. This paper specifically examines the Jewish pronunciation in terms of its use and the context in which it is mentioned in the Qur'an. The study was conducted using a qualitative approach with the type of literature study. The collected data were analyzed by the content analysis method. The results of the analysis show that the use of Jewish pronunciation in the Koran is quite diverse. The Hebrew word and its derivatives are mentioned 30 times. Jewish pronunciation consists of six forms. Respectively اليهود (al-yahūd), يهوديا(yahūdiyā), هادوا (hādū), هدنا (hudnā), هود(hūdun), and lafaz هودا(hūdā). Jewish words in the Koran are mentioned in various contexts. It is sometimes mentioned in the context of the conflict between Jews and Christians, the prohibition of Muslims from choosing a leader from the Jews, the strict attitude of the Jews, claiming to be children and lovers of Allah, the disobedience of the Jews to the Koran, and in the context of the Jews being the most hostile to Islam. Yahudi merupakan salah satu istilah yang disebutkan dalam Alquran. Tulisan ini secara khusus meneliti lafaz Yahudi dalam kaitan dengan penggunaan dan konteks penyebutannya dalam Alquran. Kajian dilakukan dengan menggunakan pendekatan kualitatif dengan jenis studi pustaka. Data yang terkumpul dianalisis dengan metode analisis isi. Hasil analisis menunjukkan bahwa penggunaan lafaz Yahudi dalam Alquran cukup beragam. Lafaz Yahudi dan turunannya disebutkan sebanyak 30 kali. Lafaz Yahudi terdiri dari enam bentuk. Masing-masing اليهود (al-yahūd), يهوديا (yahūdiyā), هادوا (hādū), هدنا (hudnā), هود (hūdun), dan lafaz هودا (hūdā). Lafaz Yahudi dalam Alquran disebutkan dalam beragam konteks. Adakalanya disebutkan dalam konteks pertentangan antara Yahudi dengan Nasrani, larangan Muslim memilih pemimpin dari Yahudi, sikap keras Yahudi, mengaku sebagai anak dan kekasih Allah, kedurhakaan orang Yahudi terhadap Alquran, dan dalam konteks Yahudi merupakan pihak yang paling memusuhi Islam.